2009
DOI: 10.1111/j.1467-6451.2009.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

CUSTOMER POACHING AND ADVERTISING*

Abstract: This paper is a first look at the dynamic effects of customer poaching in homogeneous product markets, where firms need to invest in advertising to generate awareness. When a firm is able to recognize customers with different purchasing histories, it may send them targeted advertisements with different prices. It is shown that only the firm which advertises the highest price in the first period will engage in price discrimination, a practice that clearly benefits the discriminating firm. This poaching gives ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 24 publications
1
53
1
Order By: Relevance
“…In contrast to Chen and Zhang (2009) and Esteves (2009a) where some consumers are captive and others are shoppers, here although consumers have a preference for one of the firms all of them may be induced to switch. If price discrimination is permitted it will only occur when both firms share the market in period 1.…”
Section: Related Literaturementioning
confidence: 78%
See 4 more Smart Citations
“…In contrast to Chen and Zhang (2009) and Esteves (2009a) where some consumers are captive and others are shoppers, here although consumers have a preference for one of the firms all of them may be induced to switch. If price discrimination is permitted it will only occur when both firms share the market in period 1.…”
Section: Related Literaturementioning
confidence: 78%
“…4 In a recent study Brynjolfsson and Smith (2000b) have found that Amazon customers are willing to pay up to 5-8% more before they consider switching to another seller. 5 Mixed pricing is also obtained in Chen and Zhang (2009) and Esteves (2009a).…”
Section: Related Literaturementioning
confidence: 88%
See 3 more Smart Citations